Systemanalyse - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Virtual Knowledge Communities - IT-supported Visualization and Analysis - Trier, Matthias

Systemanalyse zur Verbesserung von Geschäftsprozessen - Aier, Stephan; Haarlaender, Nico (Systemanalyse im Unternehmen : Prozessorientierte Methoden der Wirtschaftsinformatik)

Generische Transformation von Learning-Content - Das MOCCA-Projekt - Herzog, Michael A.; Trier, Matthias (Proceedings Wirtschaftsinformatik 2007)

Towards Understanding the Dynamics of Digital Communication Networks - Trier, Matthias; Bobrik, Annette; Bartels, Tilmann (Proceedings Wirtschaftsinformatik 2007)

Ein Ansatz zur prozessorientierten Evaluation von Learning Management Systemen - Luther, Michael; Trier, Matthias (Proceedings Wirtschaftsinformatik 2007)

IRIS (1978-2006) Historical Reflection through Visual Analysis - Molka-Danielsen, Judith; Trier, Matthias; Shlyk, Vadim; Bobrik, Annette; Nurminen, Markku I. (Proceedings of IRIS30, Tampere, 2007)
IRIS (Information Systems Research in Scandinavia) Conference is an annual meeting for researchers in Scandinavia. Through 29 annual conference meetings a social network of co-authorships and general research collaboration has emerged. This article contributes a historical reflection and analysis of the social network of researchers associated with the IRIS in the period from 1978 to 2006. We make use of the network visualization and analysis tool called Commetrix. We will examine the influence of certain researchers in this network by identifying their betweenness centrality and degree centrality. We will reflect on the nature and characteristic of the research topics by analyzing the network of keywords found in the conference paper titles, and visualizing their representation in the network.

Content und Kommunikation: Von der Dichotomie zur Kombination - Trier, Matthias (Content Engineering)

Systemanalyse im Wissensmanagement - Trier, Matthias; Bobrik, A. (Systemanalyse im Unternehmen - Prozessorientierte Methoden der Wirtschaftsinformatik)

Systemanalyse - Krallmann, Hermann; Trier, Matthias (Systemanalyse im Unternehmen - Prozessorientierte Methoden der Wirtschaftsinformatik)
Keywords: Prozessorientierung Systemanalyse Wirtschaftsinformatik ITeG_233

Systemtheorie und Modell - Trier, Matthias; Bobrik, A.; Neumann, N.; Wyssussek, B. (Systemanalyse im Unternehmen – Prozessorientierte Methoden in der Wirtschaftsinformatik)

Modellüberblick - Bobrik, A.; Trier, Matthias (Systemanalyse im Unternehmen – Prozessorientierte Methoden in der Wirtschaftsinformatik)

Projektmanagement - Frank, H.; Trier, Matthias (Systemanalyse im Unternehmen – Prozessorientierte Methoden in der Wirtschaftsinformatik)

IT-gestützte Visualisierung und Analyse von virtuellen Kontaktnetzwerken - Anwendungsfelder, Methodik und Vorteile - Bobrik, A.; Trier, Matthias (Analyse sozialer Netzwerke und Social Software - Grundlagen und Anwendungsbeispiele)

Production engineering for video based e- and m-learning content - Herzog, Michael A.; Trier, Matthias; Sieck, Jürgen (Proceedings of UNESCO International Centre for Engineering Education (UICEE) 10th Baltic Seminar on Engineering Education)

Towards a Social Network Intelligence Tool for visual Analysis of Virtual Communication Networks - Trier, Matthias (Virtuelle Organisationen und Neue Medien)

IT-gestützte Modellierung und Analyse elektronischer Expertengemeinschaften (Modeling and Evaluation of Electronic Expert Communities) - Trier, Matthias (i-com)

Process-Oriented Production of Learning Units for Sustainable E-Learning Offerings - Müller, Claudia; Trier, Matthias; Herzog, Michael A. (E-Learning)

A Tool for IT-supported Visualization and Analysis of Virtual Communication Networks in Knowledge Communities - Trier, Matthias (Wirtschaftsinformatik 2005)

A Procedural Model for the Production of Reusable and Standard-Compliant E-Learning Offerings - Müller, Claudia; Trier, Matthias (Wirtschaftsinformatik 2005)

IT-Supported Visualization of Knowledge Community Structures - Trier, Matthias (Proceedings of the 38th Annual Hawaii International Conference on System Sciences)

Netzwerkorientiertes Wissensmanagement und seine Unterstützung durch Softwarewerkzeuge - Krallmann, Hermann; Trier, Matthias (Strategisches Wertschöpfungsmanagement in dynamischer Umwelt: Festschrift für Erich Zahn)

Effiziente Videoproduktionsprozesse fuer komponentenbasierte E-Learning Inhalte - Trier, Matthias; Müller, Claudia; Herzog, Michael (Proceedings Potsdamer Multimedia Konferenz 2004)

Konzepte für die Videoproduktion in virtuellen Lernszenarien Beitrag zum Kollegiatentag 2004 des SVKB - Herzog, Michael A.; Trier, Matthias

IT-Supported Monitoring and Analysis of Social Networks in Virtual Knowledge Communities - Trier, Matthias (Proceedings Sunbelt XXIV Conference, Portoroz, Slovene, INSNA Association, 2004)

Measuring Brokering Activity - a novel measure for dynamic network evolution - Trier, Matthias; Bobrik, A. (Proceedings Sunbelt XXVII Conference, Corfu, Greece, INSNA Association, 2007.)

Einsatzbarrieren fuer Produktkonfiguratoren in der Automatisierungstechnik - Ergebnisse einer empirischen Untersuchung - Szydlowski, M.; Greve-Ecker, I.; Trier, Matthias (Industrie Management Journal 1/2003)

Anforderungen an die IT-Unterstuetzung für Communities of Practice im Unternehmen (in German) - Trier, Matthias (Industrie Management Journal)

Der 'Short-Clip' als Ansatz zur Produktion von video-basiertem E-Learning Content bei der VGU (in German) - Trier, Matthias; Herzog, Michael; Krallmann, Hermann (Proceedings Wirtschaftsinformatik 2003)

Integrating Communities of Practice with e-learning platforms to improve on-the-job-learning - Trier, Matthias (Proceedings of Organizational Knowledge, Learning and Capabilities Conference OKLC 2003, Barcelona, 13. April 2003.)
In knowledge intense business processes, a complex and dynamic body of knowledge is being built bottom-up by experience learning during exception handling and problem solving. Traditional qualification programs do not very effectively provide the special skills required. Communities of Practice are better supporting this dynamic on-the-job learning across hierarchies. Still, CoP approaches and platforms in many organisations can be improved by enriching them with e-learning components to create a connection between the unstructured personalisation strategy of CoPs and the structured training materials. Similarly, e-learning benefits from being linked to communities. In the article, the connections of both areas are analysed to derive a framework for integration. It proposes an agenda of activities for the two domains people-oriented and content-oriented integration of community management and e- learning. These two aspects affect the handling, configuration and design of software features. In a first stage, the challenge is mainly a management and organisational task. Consecutively, the integration processes can be further assessed in order to identify potentials for IT-automatisation.

IT-unterstuetztes Management virtueller Communities of Practice (in German) - Trier, Matthias (Proceedings DoIT Congress 2003, 24.11.2003)

Communities - Management und Unterstuetzung (in German) - Trier, Matthias (Wissensmanagement, Strategien, Prozesse, Communities)

Wissensmanagement - Schoenherr, M.; Trier, Matthias (Systemanalyse im Unternehmen)

IT-Unterstützung im Customer Relationship Management - Trier, Matthias (Industrie Management Journal)